Comparing the effects of dynamic versus static representations of land use change in hydrologic impact assessments. (December 2019) - Wagner, Paul D.; Bhallamudi, S. Murty; Narasimhan, Balaji; Kumar, Shamita; Fohrer, Nicola; Fiener, Peter
Abstract: Representations of land use change in hydrologic impact assessment studies mostly rely on static land use information of two points in time, even though the availability of dense time series of land use data allows for the incorporation of dynamic land use changes. We compare the hydrologic impacts of dynamic land use change assessments to those of static land use change assessments. These effects are illustrated with the help of two land use scenarios applied to a hydrologic model of a rapidly developing meso-scale (2036 km 2 ) catchment upstream of Pune, India. The results show that a linear dynamic land use development could be better approximated with the static approach than a non-linear development. An analysis of the impact of the frequency of land use updates indicates that the prediction of non-linear land use change impacts already improves substantially when frequent land use information every five to nine years is used. Highlights: Frequency of required land use information depends on the development rate of land use change. Non-linear land use change scenarios are hard to approximate with static land use change assessments. Land use information every five to nine years meant a pronounced improvement of prediction accuracy.